Lethal Autonomous Weapons Systems and the Right to Life in Non-Combat Contexts - Kazimi, Omida; Sefriani, Sefriani; Tolo, Arezo (Lex Renaissance, 2025)
Artificial intelligence (AI) fundamentally transformed the new technology era, particularly in the field of military and law enforcement. Lethal Autonomous Weapons Systems (LAWS) that can identify, select, and attack targets without human intervention present serious challenges regarding the right to life under IHRL. This research analysis deployment of LAWS in non-combat situations like law enforcement, border control, and counter terrorism. The current research utilizes a doctoral research method based on the Human Rights and Technology theoretical framework to analyze the international instruments such as ICCPR, UDHR, and General Comment No. 36 of the Human Rights Committee. The research finding indicates deployment of LAWS without human meaningful control violates the fundamental principles for the protection of the right to life, including the necessity principle, the proportionality principle, and accountability. LAWS is used in some countries in non-combat situations like the US, South Korea, and Israel, which have revealed that the current international framework is not able to regulate and hold responsible against unlawful killings. Therefore, violation of human dignity and an accountability gap are the consequences of delegating life and death decisions to machines without human judgment. To conclude, to regulate, monitor, human meaningful control, accountability, and protection of the right to life in the era of digital transformation, the ratification of a binding international treaty is urgently required.